Odpowiedzi

2010-03-02T10:11:23+01:00
F(x) = - 7x2 + 5,
f(x) = 2x2 + 6x,
f(x) = 2(x - 1)2 - 3
y = 2x2 + 6x + 9;
y = x2 + 4x + 4;
y = 1/2x2 + x - 4.
1 5 1
2010-03-02T10:47:09+01:00
Y = 2x² +4x +2
y = 3x²+ 2x -5
y = -5x² - x -1
y = 2x² + 4x -2
y = -5x²-x -1
y= 6x² -2x - 1
y = -6x² +2x +1
y = x² -2x -1
y = 2x² +3y +4
y = -x² -4
y = x²+2
y = 4x² + 4x +1
f (x) = x² -6x +5
f(x) = x²-10x +25
f(x) = 2x² +3x - 8
f(x) = 2x ²+5x - 3
f(x) = 3x² - 7x +2
f(x) = 6x²+x+1
f(x) _ x ²14x - 49
f(x) = 6x² + x -1
f(x) =x² +x +1
f(x) =x² +2x +3
f(x) =2x² + 6 +1

wszystkie obliczałam w szkole pozdrawiam pa
proszę o naj